Transformational and Adaptive Leadership in Times of Crisis: Lessons from COVID-19 - Nazib, Fiqra Muhamad; Anisah, Ani Siti; Usman, Asep Tutun (Indonesian Scientific Publication, 2025)
This study presents a narrative review of educational leadership in crisis contexts, with particular attention to the disruptions caused by the COVID-19 pandemic. The aim is to identify leadership strategies that supported institutional resilience, sustained learning, and safeguarded the well-being of educators and students. Literature was collected from major academic databases, including PubMed, ERIC, Scopus, and Google Scholar, using keyword combinations such as “educational leadership,” “crisis,” “COVID-19,” and “implementation strategies.” Inclusion criteria restricted the review to peer-reviewed articles addressing leadership practices during crises, while exclusion criteria eliminated non-academic and methodologically weak sources. Selected studies included case analyses, cohort studies, and theoretical papers, which were synthesized thematically. The results reveal that transformational and adaptive leadership models were most effective in enabling institutions to respond to crises. Transformational leaders motivated and inspired staff, while adaptive leaders responded flexibly to emergent challenges. Supportive institutional environments further enhanced resilience by promoting collaboration, resource-sharing, and staff engagement. Global comparisons show that leaders in developed countries relied heavily on technological innovation and robust infrastructures, whereas leaders in developing countries focused on equity and community-based strategies to sustain access. Systemic barriers, such as insufficient resources, weak infrastructures, and bureaucratic inefficiencies, were identified as major obstacles. These findings underscore the urgency of systemic reforms and leadership development initiatives. Policy interventions should prioritize equitable funding, digital infrastructure, and training in adaptive and transformational leadership. Future research must address long-term leadership outcomes and culturally grounded practices, ensuring education systems are better equipped to withstand future crises.